Os efeitos da estrutura de habitat sobre as comunidades de aranhas em uma floresta de caatinga do nordeste brasileiro - Araújo, Nicholas Sebastian Aires de (2013)
The inherent complexity of natural communities is a challenge to our understanding about how the habitat influences the abundance, local distribution and species diversity. The habitat can influence community structure in multiple ways and elucidate these relationships has provoked a lot of debate in ecology. The habitat heterogeneity hypothesis states that an increase in habitat heterogeneity (number of habitats) leads to an increase in species diversity in the landscape due to an expansion in niche dimensions. This study aims to identify whether this hypothesis is valid for the spiders that inhabit a locality in the Caatinga of northeastern Brazil. Cursorial and arboreal spiders were sampled in 30 plots within an area of Caatinga together with measures of environmental complexity, habitat heterogeneity and environmental parameters related to multiple aspects of vegetation architecture and species composition of woody plants. Stepwise multiple regressions were used to define which local environmental parameters best explain the variation in arboreal and cursorial spiders richness. Then a NMDS (Nonmetric multidimensional scaling) was used to reduce the number of predictive variables to those who are the most important and best represent the variation in spiders richness associated with the environment they were sampled. The results show a clear segregation between the guilds of arboreal and cursorial spiders, both related to what kind of environmental variables best explain its variation as well as in relation to what part of the vegetation they occupy